Resurgence of measles cases in Brazil (Research, Society and Development, 2022)
Introduction: Measles is an acute and severe disease, common in childhood, viral in nature, exanthematous, infectious, and transmissible, with the following main symptoms: high fever, above 38.5°C, generalized maculopapular exanthema, coryza, cough, conjunctivitis and Koplik's wounds. Objective: To analyze the causes of the resurgence of measles in Brazil, in the period 2010-2020. Method: This is an epidemiological, descriptive, retrospective and quantitative study, using secondary data from the Sistema de Informação de Agravos de Notificação (SINAN), Programa Nacional de Imunizações (PNI), Boletins Epidemiológicos do Sarampo e pela Informe Técnico da 8ª Campanha Nacional de Seguimento e Vacinação de Trabalhadores da Saúde contra o Sarampo. Results/Discussion: This study revealed that the return of measles cases in Brazil in recent years is associated with incomplete vaccination coverage, low vaccination rates, mobility of people from different locations, false news, neglect of public health management, population misinformation on the subject, and the increase in anti-vaccine campaigns. Conclusion: Vaccination is the most effective and safe way to fight measles. Such justification is considered necessary, therefore, vaccination campaigns should be conducted annually to achieve the vaccination coverage recommended by the Ministry of Health, to report information about the safety of vaccination and that it does not cause side effects, being one of the best strategies to remedy the Fake News.